Modelling focused electron beam induced deposition beyond Langmuir adsorption - Sanz-Hernández, Dédalo; Fernández-Pacheco, Amalio (Beilstein Journal of Nanotechnology, 2017)
In this work, the continuum model for focused electron beam induced deposition (FEBID) is generalized to account for multilayer adsorption processes. Two types of adsorption energies, describing both physisorption and spontaneous chemisorption, are included. Steady state solutions under no diffusion are investigated and compared under a wide range of conditions. The different growth regimes observed are fully explained by relative changes in FEBID characteristic frequencies. Additionally, we present a set of FEBID frequency maps where growth rate and surface coverage are plotted as a function of characteristic timescales. From the analysis of Langmuir, as well as homogeneous and heterogeneous multilayer maps, we infer that three types of growth regimes are possible for FEBID under no diffusion, resulting into four types of adsorption isotherms. We propose the use of these maps as a powerful tool for the analysis of FEBID processes.
Keywords: adsorption isotherm theory; BET model; continuum model; focused electron beam induced deposition; 3D nanoprinting; Langmuir model

(untitled) - Utke, I.; Hoffmann, P.; Melngailis, J. (J. Vac. Sci. Technol., B, 2008)

(untitled) - van Dorp, W. F.; Hagen, C. W. (J. Appl. Phys., 2008)

(untitled) - Huth, M.; Porrati, F.; Schwalb, C.; Winhold, M.; Sachser, R.; Dukic, M.; Adams, J.; Fantner, G. (Beilstein J. Nanotechnol., 2012)

(untitled) - van Dorp, W. F.; Lazić, I.; Beyer, A.; Gölzhäuser, A.; Wagner, J. B.; Hansen, T. W.; Hagen, C. W. (Nanotechnology, 2011)

(untitled) - Wu, H.; Stern, L. A.; Xia, D.; Ferranti, D.; Thompson, B.; Klein, K. L.; Gonzalez, C. M.; Rack, P. D. (J. Mater. Sci.: Mater. Electron., 2014)

(untitled) - Fernández-Pacheco, A.; Serrano-Ramón, L.; Michalik, J. M.; Ibarra, M. R.; De Teresa, J. M.; O’Brien, L.; Petit, D.; Lee, J.; Cowburn, R. P. (Sci. Rep., 2013)

(untitled) - Córdoba, R.; Sharma, N.; Kölling, S.; Koenraad, P. M.; Koopmans, B. (Nanotechnology, 2016)

(untitled) - Winkler, R.; Schmidt, F.-P.; Haselmann, U.; Fowlkes, J. D.; Lewis, B. B.; Kothleitner, G.; Rack, P. D.; Plank, H. (ACS Appl. Mater. Interfaces, 2017)

(untitled) - Jesse, S.; Borisevich, A. Y.; Fowlkes, J. D.; Lupini, A. R.; Rack, P. D.; Unocic, R. R.; Sumpter, B. G.; Kalinin, S. V.; Belianinov, A.; Ovchinnikova, O. S. (ACS Nano, 2016)

(untitled) - Geier, B.; Gspan, C.; Winkler, R.; Schmied, R.; Fowlkes, J. D.; Fitzek, H.; Rauch, S.; Rattenberger, J.; Rack, P. D.; Plank, H. (J. Phys. Chem. C, 2014)

(untitled) - Haverkamp, C.; Höflich, K.; Jäckle, S.; Manzoni, A.; Christiansen, S. (Nanotechnology, 2017)

(untitled) - Elbadawi, C.; Toth, M.; Lobo, C. J. (ACS Appl. Mater. Interfaces, 2013)

(untitled) - Shawrav, M. M.; Taus, P.; Wanzenboeck, H. D.; Schinnerl, M.; Stöger-Pollach, M.; Schwarz, S.; Steiger-Thirsfeld, A.; Bertagnolli, E. (Sci. Rep., 2016)

(untitled) - Sachser, R.; Reith, H.; Huzel, D.; Winhold, M.; Huth, M. (ACS Appl. Mater. Interfaces, 2014)

(untitled) - Walz, M.-M.; Schirmer, M.; Vollnhals, F.; Lukasczyk, T.; Steinrück, H.-P.; Marbach, H. (Angew. Chem., Int. Ed. Engl., 2010)

(untitled) - Muthukumar, K.; Jeschke, H. O.; Valentí, R.; Begun, E.; Schwenk, J.; Porrati, F.; Huth, M. (Beilstein J. Nanotechnol., 2012)

(untitled) - Boyd, E. P.; Ketchum, D. R.; Deng, H.; Shore, S. G. (Chem. Mater., 1997)

(untitled) - Henry, M. R.; Kim, S.; Fedorov, A. G. (J. Phys. Chem. C, 2016)

(untitled) - Bernau, L.; Gabureac, M.; Erni, R.; Utke, I. (Angew. Chem., 2010)

(untitled) - Porrati, F.; Kämpken, B.; Terfort, A.; Huth, M. (J. Appl. Phys., 2013)

(untitled) - Vavassori, P.; Pancaldi, M.; Perez-Roldan, M. J.; Chuvilin, A.; Berger, A. (Small, 2016)

(untitled) - De Teresa, J. M.; Fernández-Pacheco, A.; Córdoba, R.; Serrano-Ramón, L.; Sangiao, S.; Ibarra, M. R. (J. Phys. D: Appl. Phys., 2016)

(untitled) - Fernández-Pacheco, A.; Streubel, R.; Fruchart, O.; Hertel, R.; Fischer, P.; Cowburn, R. P. (Nat. Commun., 2017)

(untitled) - Friedli, V.; Utke, I. (J. Phys. D: Appl. Phys., 2009)

(untitled) - Toth, M.; Lobo, C.; Friedli, V.; Szkudlarek, A.; Utke, I. (Beilstein J. Nanotechnol., 2015)

(untitled) - Fowlkes, J. D.; Winkler, R.; Lewis, B. B.; Stanford, M. G.; Plank, H.; Rack, P. D. (ACS Nano, 2016)

(untitled) - Sushko, G. B.; Solov’yov, I. A.; Solov’yov, A. V. (Eur. Phys. J. D, 2016)

(untitled) - Bishop, J.; Toth, M.; Phillips, M.; Lobo, C. (Appl. Phys. Lett., 2012)

(untitled) - Bishop, J.; Lobo, C. J.; Martin, A.; Ford, M.; Phillips, M.; Toth, M. (Phys. Rev. Lett., 2012)

(untitled) - Porrati, F.; Sachser, R.; Walz, M.-M.; Vollnhals, F.; Steinrück, H.-P.; Marbach, H.; Huth, M. (J. Phys. D: Appl. Phys., 2011)

(untitled) - Córdoba, R.; Sesé, J.; Ibarra, M. R.; De Teresa, J. M. (Appl. Surf. Sci., 2012)

(untitled) - Mulders, J. J. L.; Belova, L. M.; Riazanova, A. (Nanotechnology, 2011)

(untitled) - Hedhili, M. N.; Bredehöft, J. H.; Swiderek, P. (J. Phys. Chem. C, 2009)

(untitled) - Pugmire, D. L.; Woodbridge, C. M.; Root, S.; Langell, M. A. (J. Vac. Sci. Technol., A, 1999)

(untitled) - Rosenberg, S. G.; Barclay, M.; Fairbrother, D. H. (J. Phys. Chem. C, 2013)

(untitled) - Hauchard, C.; Pépin, C.; Rowntree, P. (Langmuir, 2005)

(untitled) - Bresin, M.; Toth, M.; Dunn, K. A. (Nanotechnology, 2013)

Colloid science - Everett, D. H. (Royal Society of Chemistry, 1983)

CELINA - a COST action

(untitled) - Wnuk, J. D.; Rosenberg, S. G.; Gorham, J. M.; van Dorp, W. F.; Hagen, C. W.; Fairbrother, D. H. (Surf. Sci., 2011)

(untitled) - Szkudlarek, A.; Szmyt, W.; Kapusta, C.; Utke, I. (Appl. Phys. A, 2014)

(untitled) - Kusunoki, I. (J. Phys. Chem., 1974)

(untitled) - Brunauer, S.; Emmett, P. H.; Teller, E. (J. Am. Chem. Soc., 1938)

(untitled) - van Dorp, W. F.; Hansen, T. W.; Wagner, J. B.; De Hosson, J. T. M. (Beilstein J. Nanotechnol., 2013)

(untitled) - Menzel, D. (Surf. Interface Anal., 2006)

(untitled) - Raaen, S.; Ramstad, A. (Energy, 2005)

(untitled) - de Jong, A. M.; Niemantsverdriet, J. W. (Surf. Sci., 1990)

(untitled) - White, J. M. (J. Mol. Catal. A: Chem., 1998)

(untitled) - White, W. B.; Rykaczewski, K.; Fedorov, A. G. (Phys. Rev. Lett., 2006)

(untitled) - Choi, J.-G.; Do, D. D.; Do, H. D. (Ind. Eng. Chem. Res., 2001)

(untitled) - van Dorp, W. F.; Wnuk, J. D.; Gorham, J. M.; Fairbrother, D. H.; Madey, T. E.; Hagen, C. W. (J. Appl. Phys., 2009)

(untitled) - Cullen, J.; Bahm, A.; Lobo, C. J.; Ford, M. J.; Toth, M. (J. Phys. Chem. C, 2015)

(untitled) - Fowlkes, J. D.; Rack, P. D. (ACS Nano, 2010)